Role of wild bird and rodents in the epidemiology of subclinical salmonellosis in finishing pigs - Andrés Barranco, Sara (2014)
Wild birds and rodents may play an important role in the dynamics of subclinical pig salmonellosis, either as the introducers of the bacteria into the farm or as receptors of an infection already established in the farm. We tried to gain further insight into the epidemiology of this infection by studying the phenotypic (i.e., serotype and antimicrobial resistance patterns) and molecular characteristics of Salmonella strains isolated from samples collected from pigs and wildlife captured in the vicinity of pig farms. Salmonella-positive pig fecal samples were identified in 56.1% of the 41 farms investigated. Birds shedding Salmonella spp. were detected in 21.4% of the farms despite the low numbers of birds captured in many farms. Most Salmonella isolates from birds (74%) did not show any antimicrobial resistance (AR) pattern and belonged to phage types rarely seen in the pig population (U310, DT56, DT137, DT164), supporting the likely avian source of infection for most birds. The proportion of farms showing Salmonella-infected rodents was higher (46.2%), with Salmonella isolates showing a high homology with those likely originated from pigs. Salmonella-positive environmental samples were found in >50% of the farms, and the characteristics of these Salmonella strains supported the idea of pigs as a major source of Salmonella contamination of the farm environment. Dissemination of Salmonella in pig farms from areas of high Salmonella prevalence appeared to depend to some extent upon rodents and wild birds present in the farm, but the role of rodents in its maintenance seemed to be somewhat more relevant than that of birds. In conclusion, activities aimed at reducing the contact of these wild species with pigs will probably assist in the control of pig salmonellosis. Strict hygienic measures should be considered in areas of high prevalence of infection to lower the high load of environmental contamination.